2012
DOI: 10.7594/revbio.09.03.13
|View full text |Cite
|
Sign up to set email alerts
|

Interação entre sincronizadores fóticos e sociais: repercussões para a saúde humana

Abstract: Recebido 15out10Aceito 26jul12 Publicado 27dez12Resumo. O ciclo claro/escuro é considerado o mais importante zeitgeber dos ritmos de mamíferos. No entanto, em humanos, o advento da luz elétrica alterou os padrões de sincronização. A exposição à luz artificial durante a fase escura, especialmente em função de situações de trabalho e estudo noturno, viagens transmeridianas e hábitos como TV e internet, está associada à dessincronização dos ritmos circadianos. Uma variedade de pesquisas básicas e aplicadas vem de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
4
Order By: Relevance
“…Exposure to artificial light during the dark phase, in cases of night work and study, transmeridian trips and habits such as television and the internet are associated with the desynchronization of circadian rhythms. (2) This desynchronization is maintained throughout life given the profile of contemporary men's rhythm that involves the accumulation of tasks such as work, study and night leisure. These aspects can lead to difficulty in falling asleep and inability to wake up in the morning, reflecting on the quality of studies and work.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to artificial light during the dark phase, in cases of night work and study, transmeridian trips and habits such as television and the internet are associated with the desynchronization of circadian rhythms. (2) This desynchronization is maintained throughout life given the profile of contemporary men's rhythm that involves the accumulation of tasks such as work, study and night leisure. These aspects can lead to difficulty in falling asleep and inability to wake up in the morning, reflecting on the quality of studies and work.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, social activities such as work at night cause a "desynchronization" in the circadian rhythm of sleep and may lead to serious impairment of physiological and psychological functions. 31 Given the above, in this study, night shift workers showed poorer sleep quality in relation to workers from other shifts. Nevertheless, differences with regard to duration were not found.…”
Section: Discussionmentioning
confidence: 93%
“…Esses estímulos podem alterar o ciclo vigília/sono e ajudar a explicar as diferenças encontradas nos horários de dormir e de acordar entre os adolescentes da presente amostra. Pereira et al 26 discutem que as principais consequências das interações entre os sincronizadores sociais e o ciclo claro/escuro repercutem nas questões de saúde humana. Os autores discorrem que exposições à luz azul durante a noite poderiam causar maior atraso da fase do sono em decorrência de alterações no processo circadiano.…”
Section: Variáveisunclassified